2002
DOI: 10.1291/hypres.25.77
|View full text |Cite
|
Sign up to set email alerts
|

A New Method for Evaluation of Split Renal Cortical Blood Flow with Contrast Echography

Abstract: The recent development of contrast echography has made renal enhancement possible through an intravenous injection of microbubble-based contrast. In animal models, tissue perfusion can be quantified using contrast echography by measurement of the rate at which microbubbles replenish tissue after their ultrasound-induced destruction. Our purpose in this study was to evaluate renal blood flow with contrast echography in humans. To increase the sensitivity for microbubbles, we used a combination of power Doppler … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
39
2

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(44 citation statements)
references
References 27 publications
(12 reference statements)
3
39
2
Order By: Relevance
“…They also found that this attenuation exhibited a significant positive correlation with renal plasma flow. 13) Although their period of observation of cortical enhancement was only 7 seconds, the delay in rising demonstrated by a decrease in S-P slope and reduction of peak echogenicity with progression of CKD stage observed in the early phase of our present study with 600-second observation are consistent with their findings. It seems likely that the increase in renal resistance due to the decrease in number of glomeruli and peritubular capillaries as well as narrowing of arterioles contributes to the delay in rising and reduction of peak intensity with progression of CKD stage we observed.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…They also found that this attenuation exhibited a significant positive correlation with renal plasma flow. 13) Although their period of observation of cortical enhancement was only 7 seconds, the delay in rising demonstrated by a decrease in S-P slope and reduction of peak echogenicity with progression of CKD stage observed in the early phase of our present study with 600-second observation are consistent with their findings. It seems likely that the increase in renal resistance due to the decrease in number of glomeruli and peritubular capillaries as well as narrowing of arterioles contributes to the delay in rising and reduction of peak intensity with progression of CKD stage we observed.…”
Section: Discussionsupporting
confidence: 92%
“…Almost all previous studies of renal vasculature with CEUS used first-generation contrast agents, which elicit signals by the collapse of micro-bubbles, and the observation period was too short for clear examination of the renal microvasculature. 5,13) In contrast, the second-generation enhancer Sonazoid TM has a stable phospholipid shell in each micro-bubble, and since the enhancement signals obtained with it are elicited by resonance rather than bursting of micro-bubbles, stable long-term contrast enhancement can be obtained. Although Sonazoid TM is known to be captured by the reticulo-endothelial system, after intravenous injection almost all of it remains entirely within the intravascular space without being trapped in normal small vessels.…”
Section: Discussionmentioning
confidence: 99%
“…Hosotani et al (5) compared RBF obtained by CEU, radionuclide scanning using 99m technetium-mercaptoacetyltriglycine ( 99m Tc-MAG3), and PAH in 16 patients with chronic kidney disease of various causes. The authors demonstrated a significant correlation (r ϭ 0.69, P ϭ 0.005) between CEU and RBF determined by PAH clearance.…”
Section: Discussionmentioning
confidence: 99%
“…Renal perfusion has traditionally been measured using nuclear scintigraphy [3][4][5], although recently computerized tomography (CT) [6,7], positron emission tomography (PET) [8], magnetic resonance imaging (MRI) [9], and contrast-enhanced Doppler ultrasonography have been used to assess renal blood flow [10]. Although renal angiography remains the gold standard for the diagnosis of renal artery stenosis, there is no angiographic method to assess kidney perfusion objectively.…”
Section: Introductionmentioning
confidence: 99%